1998
DOI: 10.1046/j.1365-2168.1998.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of duplex imaging and arteriography in the evaluation of lower limb arteries

Abstract: Duplex ultrasonography is reliable in detecting arterial lesions in peripheral arteries and could be used routinely in the initial evaluation of patients with lower limb arterial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
1
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 22 publications
6
36
1
4
Order By: Relevance
“…15,16 In recent years, several studies have reported on the accuracy of DUS to diagnose lesions in the femoropopliteal segment with sensitivities ranging from 60% to 90% and specificities from 43% to 100%. [6][7][8][9][10][11][12][13] Our study found a strong correlation among duplex-derived PSV and Vr and angiographic findings. Using the ROC curve analysis, we calculated sensitivities and specificities for different values of PSV and Vr and chose the cutoff values with the highest accuracy.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…15,16 In recent years, several studies have reported on the accuracy of DUS to diagnose lesions in the femoropopliteal segment with sensitivities ranging from 60% to 90% and specificities from 43% to 100%. [6][7][8][9][10][11][12][13] Our study found a strong correlation among duplex-derived PSV and Vr and angiographic findings. Using the ROC curve analysis, we calculated sensitivities and specificities for different values of PSV and Vr and chose the cutoff values with the highest accuracy.…”
Section: Discussionsupporting
confidence: 55%
“…[3][4][5] Duplex ultrasound (DUS) is a noninvasive technique for evaluation of peripheral vascular disease and previous studies have shown good agreement between DUS and DSA. [6][7][8][9][10][11][12][13] It is easy to perform, has no side effects, and is relatively inexpensive. 14 However, DUS is operator-dependent and there are concerns about reproducibility of results on different equipment.…”
mentioning
confidence: 99%
“…However, the accuracy and specificity of duplex scanning may be compromised when examining arterial segments distal to significant disease. Duplex scanning may be sufficient for planning surgical approaches for revascularization [17][18][19], but intraoperative arteriography is generally needed to confirm the selection of a distal revascularization target.…”
Section: Planning For Revascularizationmentioning
confidence: 99%
“…It is a noninvasive method that is used to provide a quick, cost-effective and well-tolerated assessment of peripheral circulation. It can be used to map out arterial disease and its accuracy in doing so has been confirmed in the literature [1,2]. However, limitations exist when attempting to visualise iliac vessels in the pelvis [3][4][5].…”
Section: Introductionmentioning
confidence: 99%